Survey of The Level Knowledge of Dribbling Skills Step Over Technique - Rizqi Romadhoni, Muhammad; Yuskhil Mushofi; Afandi, Achmad; Alfian Yahya (Universitas PGRI Palembang, 2024)
The purpose of this research is to find out whether the players of Ma Shirothul Fuqoha futsal team Malang Regency know about the dribbling skills of the step over technique because there is no data about it. This quantitative descriptive research was conducted. The subjects of this research were Ma Shirothul Fuqoha Malang Regency futsal players, consisting of 30 players. This researcher used descriptive method to conduct quantitative research. Questionnaires were used to determine student interest. In this study, the standard norms of interest classification were used to analyze the data. The results showed that the average answer was classified as